The Prospect of Integrated Rearing Between "Tiktok" (Mule Ducks) with Rice, Fish and Azolla in Dki Jakarta Province - B Bakrie; Suwandi .; L Simanjuntak (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2005)
The amount of meat-type ducks consumed by people who live in DKI Jakarta area is approximately 5 .000 heads/day . Most of these ducks are coming from traditional market or duck collecting areas in Tangerang, Karawang and Bekasi . The meat-type ducks sold in those markets are primarily the young male egg-type ducks, culled laying ducks and male/female Muscovy . Some mule ducks, a crossing between Muscovy and common ducks, are also sold in the market, but only in a small proportion of about 5% of the amount of total ducks sold at one time . An outstanding mule duck has been developed through artificial insemination between male Muscovy with female egg-type duck, which is called as Tiktok . This Tiktok has some advantage than the other meat-type duck, including faster growing, higher meat proportion, lower fat in the meat and has a softer meat texture, this makes Tiktok meat better taste than the meat of the egg-type duck . However, the Tiktok consumes a significant amount of feed, therefore it requires a higher cost for its feed . This paper will discuss a model, which may be used to reduce the cost in rearing the Tiktok so that more benefit could be obtained from various commodities under an integrated farming system . The model that is proposed in this paper is an integrated rearing of the Tiktok with rice and fish with utilization of Azolla (Azolla microphylla), a water plant . Key words : Integrated farming, mule ducks, rice, fish, Azolla